Influence of Smriti Texts to Women Leadership Development in Cooperatives - Dhungana, Sita (AMC Journal, 2021)
The patriarchy under Hindu tradition has been an issue of shaping role of female in present society. Their role in the family and in the society has been taken as supportive on financial mobilization rather in leading position as compared to men. Financial mobilization through cooperatives has been accepted as a key component for economic development of Nepalese community. It may be the appropriate way of increasing income, generating employment opportunities and eradicating poverty. This study has aimed at analysing the relationship of female leadership within the circumstances of Hindu tradition, cooperative movement, and analyzed the effect of intervention factors of financial mobilization. This article has been prepared after the analytical review of Hindu ancient literatures and present policies, social customs and traditions. Information was analyzed and impact of the variables on female leadership was assessed. The result has demonstrated that the Hindu tradition has an average positive influence on financial mobilization, while investment opportunities and intervening variables have a strong positive influence on empowering women leadership in cooperatives. The Smriti texts including Manu Smriti texts were the factors that hindered the Nepalese women to take part the leadership role in their family and the community.